Grafting of CuFe12O19 nanoparticles on CNT and graphene: Eco-friendly synthesis, characterization and photocatalytic activity. (1st March 2018) - Mahdiani, Maryam; Soofivand, Faezeh; Ansari, Fatemeh; Salavati-Niasari, Masoud
Abstract: In this work, Cufe12 O19 nanoparticles were successfully synthesized using amino acids as non-toxic reagents. To achieve the desired sample with high homogeneity and the fine size, various parameters such as calcination temperature, molar ratios of Cu +2 to Fe +3 and Cu +2 to amino acid were changed. The products were characterized by SEM, TEM, EDS, XRD and FT-IR and the optical and magnetic properties were studied by DRS and VSM analyses. Furthermore, carbon-based nanocomposites of Cufe12 O19 were prepared and the effect of carbon nanotube and graphene on the properties of this hexaferrite was investigated. Improving the electrochemical properties, shifting the absorption edge to higher energy and increasing the photocatalytic activity were the results of preparation of these nanocomposites. The high surface area induced by CNT and graphene as substrates of nanocomposites led to increase the photocatalytic activities of these composites under UV irradiation. According to the results, photocatalytic activity of graphene-based nanocomposites was better and degradation percent of Erythrosine as an anionic dye was more than the other dyes. The photocatalytic reactions followed the pseudo-first order kinetic model. Graphical abstract: Image Highlights: CuFe12 O19 nanostructures were synthesized using amino acid by eco-friendly sol-gel method. Amino acids as natural compounds can be considered as a way to decrease the environment pollutions. Amino acids act as reducing and capping agents, so they can decrease the using chemical reagents. Synthesis of carbon-based nanocomposites of CuFe12 O19 were reported in this work, at the first time.